Inflation and counter-inflationary policy measures: The case of the Netherlands - Wim Suyker (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
Dutch inflation has risen steeply recently, despite unprecedented cuts in energy taxes and VAT, to a record high of 17% in September 2022. Energy has been by far the major driver of the inflation surge, but inflation has been broadening in 2022, with food price rises above 10% since July and core inflation at 6.0% in September. There is a sizeable difference between income groups regarding the impact of inflation. In September, Dutch inflation exceeded that of the euro area by 7%-point. This is however for a considerable part due to differences in the way gas and electricity prices are measured. The year-on-year increase of negotiated wages was up to 3.6% in September 2022. However, with the pick-up of nominal wages substantially lagging that of consumer prices, real wages are dropping at a record speed. The corporate mark-up is relatively stable. Government has taken substantial measures to cushion households and companies from the effects of high inflation, with budgetary costs of 1.0% of GDP in 2022 and 3.4% in 2023. In 2022, the main measures were cuts in energy taxes, but an energy allowance of 1300 euros for low income groups was also introduced. In 2023, by far the main measure will be an energy price cap. The government deficit may rise from 1.1% of GDP in 2022 to close to 4% of GDP in 2023. The cost of living crisis has not lead to formal talks about a social pact. This is in contrast with the economic crisis in the 1980s, which led to the Wassenaar Agreement.
urn:nbn:de:101:1-2023011910301684045795
Keywords: 330; Austrian Chamber of Labour Vienna (AK Wien); Inflation; Netherlands; gas; electricity; price cap; HICP; energy; distribution; social pact; real wages